Optical Systems for Astronomy (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
This collection of papers covers a number of topics related to the astronomical optics. In particular, it describes proposed ground-based and space instruments, novel optical design concepts, telescopes alignment techniques, cryogenic systems for astronomy, adaptive optics and mirror polishing. In total, it comprises 15 research articles and 1 review, which were published as a special issue of Photonics Journal.